Adjuvant therapy for high‐risk renal cell carcinoma after nephrectomy how many trials are positive? Only one or more than one. (27th August 2020) - Ravaud, A.
Abstract: Adjuvant treatment with VEGFR tyrosine kinase inhibitor in renal cell carcinoma after nephrectomy has been reported through four clinical trials: S‐TRAC, ASSURE, PROTECT and ATLAS. Only S‐TRAC has been significantly positive on primary endpoint DFS under sunitinib compared to placebo, whereas ASSURE, PROTECT and ATLAS did not show any gain under sunitinib, sorafenib, pazopanib or axitinib, respectively. Nevertheless, there are arguments for a trend for the impact of anti‐angiogenic therapy on outcome of patients with high‐risk renal cell carcinoma cancer following nephrectomy, allowing for a fair discussion with patients to decide for or against an adjuvant treatment.